Anomalous transverse resistance in the topological superconductor β-Bi2Pd - Xiaoying Xu; Yufan Li; C. L. Chien (Nature Communications, 2022)
Centrosymmetric β-Bi2Pd is a candidate topological superconductor. Here, the authors observe a transverse voltage in β-Bi2Pd thin films and propose that this voltage is a result of chiral topological surface states.